Maturity Levels of Student Support E- Services Within an Open Distance E-learning University - Nsamba, Asteria (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
The University of South Africa (UNISA) is one of the distance education universities that is shifting from open distance learning (ODL) to open distance e-learning (ODeL). UNISA started as a correspondence institution in the 1950s and it has since evolved into an ODeL university. The aim of this research was to assess and determine the maturity levels of UNISA lecturers’ and tutors’ explorations of various forms of e-learning technologies to support students in an ODeL environment. Semi-structured interviews were conducted with 12 academic staff members. A hybrid approach involving inductive and deductive reasoning was used to guide the whole research process. The online course design maturity model (OCDMM) was modified and adapted in order to guide data collection, data analysis, and the interpretation of results. The results of the study indicate that the maturity levels of UNISA’s student support e-learning technologies are at the basic levels of the maturity assessment framework for open distance e-learning. It is hoped that the results of this research will serve as a starting point that the University can use to constantly measure improvements made in advancing e-learning activities.